2000
DOI: 10.1054/bjoc.2000.1229
|View full text |Cite
|
Sign up to set email alerts
|

Disparate responses of tumour vessels to angiotensin II: tumour volume-dependent effects on perfusion and oxygenation

Abstract: Summary Perfusion and oxygenation of experimental tumours were studied during angiotensin II (AT II) administration whereby the rate of the continuous AT II infusion was chosen to increase the mean arterial blood pressure (MABP) by 50-70 mmHg. In subcutaneous DSsarcomas the red blood cell (RBC) flux was assessed using the laser Doppler technique and the mean tumour oxygen partial pressure (pO 2 ) was measured polarographically using O 2 -sensitive catheter and needle electrodes. Changes in RBC flux with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…The lack of specificity for the tumor vs. the host vessels led, indeed, to vasomotor effects mostly dependent on the overall arrangement of these vessels (i.e., opposite if both tumor and host tissue vessels are located in parallel and similar if placed in series). Also, the proportion of functional vs. neo-formed immature vessels into the tumor is known to influence the net effects of these drugs (29). Here, we show that local delivery of ionizing radiation may bypass the specificity problem and can selectively modulate flow resistance.…”
Section: Discussionmentioning
confidence: 70%
“…The lack of specificity for the tumor vs. the host vessels led, indeed, to vasomotor effects mostly dependent on the overall arrangement of these vessels (i.e., opposite if both tumor and host tissue vessels are located in parallel and similar if placed in series). Also, the proportion of functional vs. neo-formed immature vessels into the tumor is known to influence the net effects of these drugs (29). Here, we show that local delivery of ionizing radiation may bypass the specificity problem and can selectively modulate flow resistance.…”
Section: Discussionmentioning
confidence: 70%
“…The validity of these adjuvant approaches to conventional chemo-and radiotherapy was usually verified a posteriori by documenting a better tumor response with very limited insights on the mechanisms of the tumor selectivity. Conversely, studies that did not look for a gain in treatment efficacy have identified the existence of tumor-specific vascular reactivity to various products including endothelin (18), endothelin agonist (19), angiotensin (20,21), noradrenaline (22), hemoglobin A (23), and tumor necrosis factor ␣ (24).…”
Section: Introductionmentioning
confidence: 99%
“…Although reactivity of the BCC supplying vessels (contained in healthy skin) was certain (healthy skin and BCC reacted identically during lidocaine injection, flap raising and temporary vascular occlusion), reactivity of the intra-tumoral vessels to temporary vascular occlusion remains an important question for future investigation using video-capillaroscopy, because intra-tumoral reactive vasoconstriction might have impaired the effect of PORH in tumor supplying vessels during tumor perfusion, as opposed to the vasodilatation or complete passivity of intra-tumoral vessels. However, the general immaturity of intra-tumoral vessels of malignant tumors with almost maximal vasodilatation and low vasodilatatory reserve (Suzuki et al 1981, Peterson 1991, Fukumura and Jain 1998, Vaupel et al 1998, Thews et al 2000, Isenberg et al 2008, Sonveaux et al 2009 should render those tumors vessels principally unreactive to temporary occlusion. Thus, PORH will be efficient through tumor upstream normal vessels dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…While intratumoral microvascular density is high, tumoral vessels are abnormal and chaotic (Less et al 1991;Zama et al 1991;Sharma et al 2005;Dewhirst et al 2008;Fukumura and Jain 2008), leading to perfusion-mediated hypoxia (Hill et al 1996;Kimura et al 1996;Gillies et al 1999;Cardenas-Navia et al 2004;Dewhirst et al 2007), tumor progression, and radiotherapy resistance (Gray et al 1953;Roots and Smith 1974;Vaupel 2004;Moeller et al 2007;Overgaard 2007;Vaupel 2008). Pharmacological approaches for tumors have focused on vasodilatation of the supplying vessels (Suzuki et al 1981;Peterson 1991;Fukumura and Jain 1998;Vaupel et al 1998;Thews et al 2000;Isenberg et al 2008;Sonveaux et al 2009), mainly towards increasing tumor mean partial oxygen pressure and overcoming hypoxia-induced radio-resistance, but have been fundamentally limited by its non-selectivity, thus, greatly decreasing its efficacy and increasing side-effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation